Birth decade affects the sensitization pattern and asthma risk in Finnish adult population. Issue 11 (22nd May 2017) - Toppila‐Salmi, S.; Luukkainen, A.; Lemmetyinen, R.; Karjalainen, J.; Huhtala, H.; Renkonen, R.; Wang, D. Y.; Mäkelä, M. J.; Pekkanen, J.
Abstract: We have previously shown that sensitizations to several types of allergens distinguish subjects with and without adult‐onset asthma in Finland. The aim was to analyze how age affects sensitization and asthma risk. We used previous population‐based case‐control data (N=456) from Finnish adult asthma patients with one or two matched controls. Asthma was diagnosed based on a typical history of asthmatic symptoms and lung function tests. Allergic sensitization was determined by skin prick test (SPT) to 17 aeroallergens. Information on demographics was obtained by a questionnaire. Sensitization to more than one allergen type and the number of positive SPT reactions associated with younger age and asthma. Atopic subjects aged 65 and above were characterized by sensitization to only one to two allergens, with very few animal danders and without an association with asthma. Multiple sensitizations and animal dander sensitization are more common among Finnish asthmatic adults aged under 56 than among older asthmatics. Cohort studies are needed to understand timing of host‐environmental interactions behind this.